An Examination The Factors Of Share Investment Decisions : The Mediating Role Of Behavioral Finance Cirebon Society - Sugianto, Alya Nurlaella; Mardiyani, Mardiyani (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the effect of financial literacy, financial technology, on stock investment decisions in the millennial generation in Cirebon Regency, with financial behavior as a mediating variable. This research uses a quantitative approach with a causal associative method. The research sample of 150 respondents was taken using purposive sampling technique. The data analysis technique uses statistical methods with Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the Smart-PLS 4 application. The results showed that financial literacy has no direct effect on stock investment decisions. Meanwhile, financial technology has a significant influence on investment decisions, due to easy access and innovative features that facilitate decision making. Financial literacy and financial technology also have a significant effect on financial behavior, where individuals with good financial understanding are better able to manage finances efficiently. Financial behavior is proven to be able to mediate the effect of financial literacy and financial technology on stock investment decisions. The conclusion of this study emphasizes the importance of improving financial literacy and utilizing financial technology to support healthy financial behavior, so that millennials can make smarter investment decisions. The results show that the ease of access offered by financial technology, along with healthy financial behavior, are key factors that encourage millennials to invest in the stock market. Therefore, efforts are needed to improve financial literacy, develop innovations in financial technology, and encourage the formation of good financial habits to increase the participation of millennials in the capital market.